KETENTUAN HAK CIPTA BERKAITAN DENGAN PEMBAYARAN ROYALTI ATAS PEMANFAATAN CIPTAAN LAGU SECARA KOMERSIAL PADA RESTORAN/CAFÉ DI DAERAH PARIWISATA JIMBARAN BALI - Dharmawan, N.K.S.; Landra, P.T.C.; Wiryawan, I.W.; Bagiastra, I.N.; Samsithawrati, P.A. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
The songs which are used commercially in restaurants or cafes without permission of the creators is categorized as infringing Copyright under Article 1, 4 to 9 of Law No. 28 of 2014 on Copyright (Indonesian Copyright Law). However, such commercial used of the songs is not considered as Copyright infringement as long as the users meet their obligation based on the agreement with the Collective Management institution (CMI) to pay the song royalty under Article 87 (4) of Indonesian Copyright Law. Nevertheless, the existence of this institution is not widely known by businessmen society (restaurant and cafe’s owners) in tourism areas of Jimbaran-Kedonganan Bali. The purposes of this dissemination are to provide an understanding of song Copyright protection, the importance of obligation to pay royalties by users through CMI and to prevent and minimize Copyright infringement cases. Methods used in this dissemination are brief awareness-raising lecturing session and in-depth discussion along with the distribution of Indonesian Copyright Law. The dissemination were successfully held in Kedonganan on 21 June 21 2016 and in Jimbaran on 4 August 2016 in which the participants were very enthusiastic since matter delivered is new and useful for their daily business activities.